Implementasi Perkuliahan DARING Matakuliah Pendidikan Laboratorium IPA Pada Masa Pandemi - farida Nurlaila Zunaidah (JURNAL PENDIDIKAN DASAR NUSANTARA, 2020)
Abstract: This research was conducted with the aim to describe the implementation of online lectures on Pendidikan Laboratorium IPA courses at the 4th semester of students college PGSD during the covid-19 pandemic. The method in this research is descriptive qualitative. The research data are described in the form of words that describe the stages of conducting online lectures. The results of this study are online lectures on Pendidikan Laboratoriun IPA consisting of three stages, namely the preparatory stage, the implementation stage, and the structured assignment stage in the form of reports on the results of practical activities. Keywords: implementation of online lecturer, Pendidikan Laboratorium IPA course, pandemic period